Process Evaluation of Community-Based Nutrition Service for Under 2 Years Children in Degadamot District Using Qualitative Approach, Western Ethiopia, 2023 - Teshome Demis Nimani MPH; Enyew Muluneh MPH; Geta Asrade MPH; Tesfahun Zemene MPH; Feyisa Shasho Bayisa MPH; Sara Debebe Jimma MPH (SAGE Publishing, 2024)
Malnutrition accounts for 45% of under-5 child morbidities in Ethiopia and is a more common issue in rural communities. In that regard, Ethiopia has implemented a CBN program at the community level to improve the nutrition status of children. Despite this, malnutrition still causes a significant rate of child morbidity and mortality. The implementation status of the CBN program is unknown. Thus, this evaluation aimed to evaluate the children under 2 years in Degadamot district health posts in northwest Ethiopia. A facility-based single-case study design with qualitative-method evaluation was employed from March 28 to April 28, 2023. The evaluation focused on the availability and compliance with multiple data sources. The qualitative data were transcribed, translated, and analyzed using thematic analysis with OPEN CODE version 4.02 software. Finally, the overall program implementation was determined based on predetermined judgmental criteria. According to the predetermined judgment parameter, the overall CBN program implementation level was 62.68%, measured by the availability of resources (71.36%) and compliance of service providers (54.0%). The overall community-based nutrition program implementation in the Degadamot district health post with 2 evaluation dimensions was judged as fair based on the presetting criteria. It is better to improve the service through training HEW and HDA, distributing nutritional supplies, providing regular support, and following up with HEWs for GMP performance in the Degadamot district.